2022
DOI: 10.1186/s12870-022-03961-7
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive identification and expression analyses of the SnRK gene family in Casuarina equisetifolia in response to salt stress

Abstract: Background Sucrose nonfermenting-1 (SNF1)-related protein kinases (SnRKs) play crucial roles in plant signaling pathways and stress adaptive responses by activating protein phosphorylation pathways. However, there have been no comprehensive studies of the SnRK gene family in the widely planted salt-tolerant tree species Casuarina equisetifolia. Here, we comprehensively analyze this gene family in C. equisetifolia using genome-wide identification, characterization, and profiling of expression ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
4
0
1
Order By: Relevance
“…This species grows well in areas characterized by prolonged dry seasons and lower air humidity (Djighaly et al 2018). These differences in habitat preferences reflect the adaptation of both species to specific environmental conditions that allow them to grow and develop optimally (Ai et al 2022). In Java, C. junghuhniana grows naturally at 1200-3100 m asl.…”
Section: Introductionmentioning
confidence: 99%
“…This species grows well in areas characterized by prolonged dry seasons and lower air humidity (Djighaly et al 2018). These differences in habitat preferences reflect the adaptation of both species to specific environmental conditions that allow them to grow and develop optimally (Ai et al 2022). In Java, C. junghuhniana grows naturally at 1200-3100 m asl.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have revealed that the SnRK family is a crucial component in plant signaling transduction and response to abiotic stress [50,51]. Moreover, the SnRK family members of many plants have been clarified, including Liriodendron chinense [52], Brassica napus [53], Casuarina equisetifolia [54], Brachypodium distachyon [55], cotton [56], Triticum aestivum [57] and Phaseolus vulgaris [58]. However, only a few SnRK genes of S. miltiorrhiza were cloned and studied in previous studies [59].…”
Section: Discussionmentioning
confidence: 99%
“…The most effective approach for identifying allelic variants is through the High-Resolution Melting (HRM) technique. Discrepancies observed in peptide sequences have been associated with alterations in protein conformation and the identification of cis-elements related to ABA signaling (Ai et al, 2022). The mapping of SNPs has identified two crucial TFs, DREB1 and WRKY1, which provide drought and salt tolerance (Urbanavičiūtė et al, 2021).…”
Section: Use Of Molecular Markers To Identify Drought Signaling Genesmentioning
confidence: 99%